ISLAMIC PRINCIPLES OF FINANCING INFRASTRUCTURAL PROJECTS AND FRAMEWORK STRATEGIES FOR DEVELOPMENT OF UZBEKISTAN - Ashurova Gold Yuldashevna (Ecominds Press, 2025)
V sovremennom mire islamskoe finansirovanie, osnovanoe na shariate, predlagaet eticnuyu alternativeu traditsionnym instrumentam, isklyuchaya riba , garor i maysir . In Uzbekistan, where Muslims make up 90% of the population, it is integrated into the "Strategy of Development of the Republic of Uzbekistan 2030" for financing infrastructure - roads, energy and education. Key principles: musharaka (risk distribution), mudaraba (trust management), ijjara (leasing) and sukuk (Islamic bonds), enabling permanent investment. Gosudarstvennye reforms include joining AAOIFI , creating Islamic banking and partnership with IsDB (funding of $396.7 million in 2023 for M 39 and agricultural infrastructure). Eto privlekaet do $5 billion ot OIS, diversify capital and increase social justice. The article analyzes the evolution of the sector, the effectiveness of instruments and recommendations for institutionalization, emphasizing the role of "New Uzbekistan"
Keywords: Islamic finance, Sharia-covestimye principles, infrastructural projects; sukuk , musharaka , Islamic Bank Razvitiya, ustoichivye investitsii, ekonomicheskiy rost, etichnoe finansirovanie.